Trading places [videorecording (Blu-Ray)] - Aykroyd, Dan; Murphy, Eddie, 1961-; Bellamy, Ralph, 1904-1991; Ameche, Don; Curtis, Jamie Lee, 1958-; Elliott, Denholm (Distributed by Warner Home Video, 2007)
Two millionaires test their nurture vs. nature theory when they make a Wall Street tycoon a beggar and a street hustler a Wall Street tycoon.